Cohabitation, civil partnership, marriage and the equal sharing principle. (10th July 2012) - Chan, Winnie
<x xml:space="preserve">Abstract</x> This paper explores certain questions regarding whether the law concerning relief upon the dissolution of civil partnership and cohabitation should parallel that of marriage. It will be contended that while the principle of compensation does have an important role to play in the aftermath of de facto relationships, there remain reasons not to assimilate cohabitation fully with marriage – and in particular, not to apply the key principle of equal sharing that now informs divorce settlements in many jurisdictions, including England. On the other hand, an argument against assimilating marriage with civil partnership can be grounded in the fact that a civil partnership involves two parties of the same gender. This point generates room to argue that a presumption of equal sharing – to the extent that it rests upon compensatory rationales – may be less powerful in civil partnerships. Nonetheless, that claim can be circumnavigated by the argument for equal sharing as an independent principle – one applicable to civil partnership just as much as to marriage.